In vitro digestibility of sorghum parent lines predicts nutritional value of their hybrid offspring in cannulated finishing pigs - Healy, B.J.; Bramel-Cox, P.J.; Hines, Robert H.; Hancock, Joe D. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
Nutritional value of eight sorghum hybrids, resulting from matings of four male lines with two male-sterile lines, was determined. The male lines were two sorghums with consistently high in vitro digestibility (High-digestibility 1 and Highdigestibility 2) and two sorghums with consistently low in vitro digestibility (Lowdigestibility 1 and Low-digestibility 2). The male-sterile lines were Kansas 52 and Redlan, two lines commonly used for genetic testing by sorghum breeders. The hybrids were fed to eight barrows fitted with ileal T-cannulas and also evaluated for starch digestibility in ruminal fluid. Corn was used as a control. Corn had greater ileal and total tract digestibilities of DM, GE, N, and starch than the hybrids, but was similar to the sorghums for starch digestibility in ruminal fluid. Ileal digestibilities were not different for the male-sterile parent lines, but hybrids of Kansas 52 had greater DM, GE, and N digestibilities over the total tract than hybrids of the Redlan parent line. Among the male parent lines, hybrids from the two lines with high in vitro digestibility had greater total tract digestibilities of DM, GE, and N than lines with low in vitro digestibilities. In conclusion, selection based on our laboratory procedure was an effective predictor of total tract nutrient digestibility of sorghum in pigs. Also, differences among parent lines for nutrient digestibility were still evident in their hybrid offspring.
Keywords: Swine; Finishing; Sorghum; Digestibility; In vitro